Soil moisture estimation using Sentinel-1 SAR and field observation in the Eastern Ghats region of India - Uday Mandal; M. Madhu; Ramajayam Devarajan; Randhir Kumar; Gopal Kumar; HC Hombegowda; SK Samal; Saswat Kumar Kar; P. Raja; Pyla Sravani; Sitanshu Sekhar Patra (Environmental Monitoring and Assessment, 2026)

Quantitative assessment of modern pollen analogue from Majuli Island, Northeast India: insights into vegetation–climate dynamics and human impact - Arya Pandey; Swati Tripathi; Pujarini Samal; P. Morthekai; Hema Singh (Environmental Monitoring and Assessment, 2026)

sCentInDB: a database of essential oil chemical profiles of Indian medicinal plants - Shanmuga Priya Baskaran; Geetha Ranganathan; Ajaya Kumar Sahoo; Kishan Kumar; Jayalakshmi Amaresan; Kundhanathan Ramesh; R. P. Vivek-Ananth; Areejit Samal (Molecular Diversity, 2026)
Essential oils are complex mixtures of volatile compounds produced by aromatic plants and widely used in personal care, food flavoring, and pharmaceutical industry due to their odor and therapeutic properties. As a high-value and low-volume organic product, optimizing plant yield and modifying composition by leveraging knowledge on chemical profiles of essential oils can lead to enhanced bioproducts. Additionally, overharvesting of wild medicinal plants, especially in India, threatens biodiversity. Essential oil profiles of such plants can help regulate their exploitation. Here, we present sCentInDB, a manually curated FAIR-compliant DataBase of Essential oil Chemical profiles of Medicinal plants of India, compiled from published literature. sCentInDB contains data on 554 Indian medicinal plants at the plant part level, encompassing 2170 essential oil profiles, 3420 chemicals, 471 plant-part-therapeutic use associations, 120 plant-part-odor associations, and 218 plant-part-color associations. sCentInDB also compiles metadata such as sample location, isolation, and analysis methods. Subsequently, an extensive analysis of the chemical space in sCentInDB was performed. By constructing a chemical similarity network, terpenoids were found to be distributed across the network, indicating greater structural diversity. Moreover, a comparison of the scaffold diversity of chemicals in sCentInDB was performed against three other aroma libraries using cyclic system retrieval curves. Altogether, sCentInDB will serve as a valuable resource for researchers working on plant volatiles and employing genetic engineering to enhance oil yield and composition. Further, sCentInDB will aid in the establishment of quality standards for essential oils and provide vital insights for therapeutic and perfumery applications. sCentInDB is accessible at https://cb.imsc.res.in/scentindb/ . Graphical abstract Graphical abstract summarizing the workflow for constructing the sCentInDB database and analysis of the associated chemical space.

Impact of Land Use Change on Soil Hydraulic Conductivity Characteristics Under Saturated and Near-Saturated Conditions for the Vulnerable Eastern Ghats Region of India - S. K. Vishwakarma; R. M. Singh; S. Patra; S. K. Kar; H. C. Hombegowda; S. K. Samal; P. Raja; R. Devarajan (Agricultural Research, 2026)

Assessing the anaerobic biodegradability of PHB filament and its 3D printed sheets through biochemical methane potential (BMP) test - Anita Jena; Anjaly P. Thomas; Bijaya Bikram Samal; Brajesh Kumar Dubey; Cheruvu Siva Kumar; Shailendra Kumar Varshney (Science of The Total Environment, 2025)

Geospatial and machine learning-based coastal vulnerability assessment of Puri, Odisha - Nihar Ranjan Parida; Subhasmita Parida; Pinaki Samal; Abisha P (Journal of Coastal Conservation, 2025)

Fisheries Sustainability of Tampara Lake, a Ramsar Site in Eastern India - S. Parida; P. K. Parida; R. N. Samal; P. R. Swain (Proceedings of the Zoological Society, 2025)

Multidecadal wet and dry phases during the Little Ice Age: Palynofacies, dinoflagellate cysts and palynological evidence from the western Bay of Bengal - Prem Raj Uddandam; Pujarini Samal; Jyoti Srivastava; Abha Singh; Shalin K Hari; Abhi S Krishna; P Morthekai (Journal of Earth System Science, 2025)

Nature’s allies: Unleashing the potential of oxalic acid-modified Saccharum spontaneum (kashful stalks) for methylene blue removal from water and wastewater - Md. A. Qaiyum; B. Bharadwaj; P. P. Samal; B. Dey; S. Dey (International Journal of Environmental Science and Technology, 2024)

Relative survival and detoxification enzyme activity in Dysdercus koenigii (Hemiptera: Pyrrhocoridae) exposed to β-cyfluthrin alone and its nanometric emulsion - P. Lanbiliu; Roopa Rani Samal; Kungreiliu Panmei; Sarita Kumar (Phytoparasitica, 2024)

Hydrolytic genes of antagonistic rhizobacteria strains on Fusarium udum causing wilt disease in pigeonpea - Swarnmala Samal; Dinesh Singh; Ram Sanmukh Upadhyay; P. Lokesh Babu; Neelam Geat (Journal of Plant Pathology, 2024)

Dye sequestration from aqueous phase using natural and synthetic adsorbents in batch mode: present status and future perspectives - R. Kumari; J. Mohanta; B. Sambasivaiah; M. A. Qaiyum; B. Dey; P. P. Samal; S. Dutta; S. Dey (International Journal of Environmental Science and Technology, 2023)

Towards a circular economy: chemical packaging waste as a promising scavenger for Neutral red from water and wastewater - P. P. Samal; M. A. Qaiyum; S. Dutta; J. Mohanta; B. Dey; S. Dey (International Journal of Environmental Science and Technology, 2023)

In silico identification of potential inhibitors of vital monkeypox virus proteins from FDA approved drugs - Ajaya Kumar Sahoo; Priya Dharshini Augusthian; Ishwarya Muralitharan; R. P. Vivek-Ananth; Kishan Kumar; Gaurav Kumar; Geetha Ranganathan; Areejit Samal (Molecular Diversity, 2023)

Heavy metal contamination assessment and its associated human health risk evaluation in the Mahanadi River sediments, India - P. Samal; S. R. Singarasubramanian; M. C. Manoj; J. Srivastava; N. Dsouza; K. Balakrishna; M. M. Chauhan; S. Ali (International Journal of Environmental Science and Technology, 2023)

Potential phytochemical inhibitors of SARS-CoV-2 helicase Nsp13: a molecular docking and dynamic simulation study - R. P. Vivek-Ananth; Sankaran Krishnaswamy; Areejit Samal (Molecular Diversity, 2022)

Influence of lufenuron on the nutrient content and detoxification enzyme expression in Aedes aegypti L. (Diptera: Culicidae) - Kungreiliu Panmei; Roopa Rani Samal; P. Lanbiliu; Sarita Kumar (International Journal of Tropical Insect Science, 2021)

Stable quantitative trait locus (QTL) for sheath blight resistance from rice cultivar CR 1014 - Archana Bal; Pankajini Samal; Mridul Chakraborti; Arup Kumar Mukherjee; Soham Ray; Kutubuddin A. Molla; Lambodar Behera; Rashmita Samal; Sarmistha Sarangi; Pritiranjan Sahoo; Motilal Behera; Srikanta Lenka; et al. (Euphytica, 2020)

Spit and Inlet Morphodynamics of a Tropical Coastal Lagoon - M. M. Mahanty; P. K. Mohanty; S. Pradhan; R. N. Samal; V. Ranga Rao (Marine Geodesy, 2019)

Land Cover Mapping for Namdapha National Park (Arunachal Pradesh), India Using Harmonized Land Cover Legends - Mahendra S. Lodhi; Prasanna K. Samal; Shivaji Chaudhry; L. M. S. Palni; P. P. Dhyani (Journal of the Indian Society of Remote Sensing, 2014)

Diversity of epiphytic lichens and their role in sequestration of atmospheric metals - S. Kar; A. C. Samal; J. P. Maity; S. C. Santra (International Journal of Environmental Science and Technology, 2014)

Evaluation of genetic diversity among commercial cultivars, hybrids and local mango (Mangifera indica L.) genotypes of India using cumulative RAPD and ISSR markers - K. C. Samal; R. C. Jena; S. S. Swain; B. K. Das; P. K. Chand (Euphytica, 2012)

Arsenic Contamination in Rice, Wheat, Pulses, and Vegetables: A Study in an Arsenic Affected Area of West Bengal, India - P. Bhattacharya; A. C. Samal; J. Majumdar; S. C. Santra (Water, Air, & Soil Pollution, 2010)

Accumulation of arsenic and its distribution in rice plant (Oryza sativa L.) in Gangetic West Bengal, India - P. Bhattacharya; A. C. Samal; J. Majumdar; S. C. Santra (Paddy and Water Environment, 2010)

Production of antibacterials from the freshwater alga Euglena viridis (Ehren) - B. K. Das; J. Pradhan; P. Pattnaik; B. R. Samantaray; S. K. Samal (World Journal of Microbiology and Biotechnology, 2005)

Genetic relatedness in cashew (Anacardium occidentale L.) germplasm collections as determined by randomly amplified polymorphic DNA - S. Samal; P.C. Lenka; R.M. Nanda; S. Nayak; G.R. Rout; P. Das (Genetic Resources and Crop Evolution, 2004)

Rescue of a bovine respiratory syncytial virus genomic RNA analog by bovine, human and ovine respiratory syncytial viruses confirms the “functional integrity” and “cross-recognition” of BRSV cis-acting elements by HRSV and ORSV - A. S. Yunus; S. Krishnamurthy; M. K. Pastey; Z. Huang; S. K. Khattar; P. L. Collins; S. K. Samal (Archives of Virology, 1999)